2019
DOI: 10.1186/s12871-019-0790-y
|View full text |Cite
|
Sign up to set email alerts
|

Validity of accuracy and trending ability of non-invasive continuous total hemoglobin measurement in complex spine surgery: a prospective cohort study

Abstract: Background Patients undergoing complex spine surgery present with multilevel spinal involvement, advanced age, and multiple comorbidities. Surgery is associated with significant blood loss and remarkable hemodynamic changes. The present study aimed to investigate the accuracy and trending ability of a non-invasive continuous method to monitor hemoglobin (SpHb) concentrations using a Radical-7™ Pulse CO-Oximeter in complex spine surgery. Methods Forty-nine patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…Data were collected over a period of almost 10 years, during which the algorithm for calculating non-invasive Hb is claimed to have been improved. However, more recent work on Hb during spinal surgery and liver transplantation [ 10 , 19 ] show almost identical accuracy and precision for the non-invasive Hb as we reported in 2010 [ 2 ]. These authors also studied the concordance between changes in invasive and non-invasive Hb during surgery [ 10 , 19 ].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Data were collected over a period of almost 10 years, during which the algorithm for calculating non-invasive Hb is claimed to have been improved. However, more recent work on Hb during spinal surgery and liver transplantation [ 10 , 19 ] show almost identical accuracy and precision for the non-invasive Hb as we reported in 2010 [ 2 ]. These authors also studied the concordance between changes in invasive and non-invasive Hb during surgery [ 10 , 19 ].…”
Section: Discussionsupporting
confidence: 75%
“…However, more recent work on Hb during spinal surgery and liver transplantation [ 10 , 19 ] show almost identical accuracy and precision for the non-invasive Hb as we reported in 2010 [ 2 ]. These authors also studied the concordance between changes in invasive and non-invasive Hb during surgery [ 10 , 19 ]. However, we chose to present our results differently, as we obtained data at very short intervals, usually only 5–10 min, and up to 25 times per experiment.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Studies of 48 vascular surgery patients [ 17 ] and of 70 patients undergoing major orthopedic surgery [ 18 ] concluded SpHb had clinically acceptable trending with ABGHb or tHb. In 49 patients undergoing spine surgery, change concordance was 85.1% when excluding SpHb with perfusion index under 1 [ 19 ]. When using the exclusion zones determined by measurement repeatability analysis but not excluding SpHb based on low perfusion index, SpHb concordance was 94.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown a negative biasness <1 g/dL in SpHb values on different surgical subsets. [ 13 14 ] Considering the magnitude of SpHb-tHb difference, 60% values fall within 1 g/dL, 23% were between 1 and 2 g/dL, and 17% were >2 g/dL, respectively. Butwick et al .…”
Section: Discussionmentioning
confidence: 99%